2014
DOI: 10.3109/09513590.2014.936847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estroprogestins containing natural estrogen on vaginal flora

Abstract: Estroprogestins with "natural oestrogen" has represented a new option in terms of combined hormonal contraception. So, the aim of this study is to investigate how estroprogestins with natural estrogen may modify the vaginal niche. In literature, very few studies focused on the interaction between hormonal contraception and vaginal milieu. This is a prospective comparative study. We enrolled 60 women from January 2013 to September 2013, 30 of them were administered estradiol valerate dienogest (E2V+DNG - Klaira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Sex hormones strongly affect the overall structure and function of vaginal microbiota (Hillier, 2011;Kaur et al, 2020). In general, vaginal microbiota is relatively balanced and stable, whereas genetic, ethnic, environmental, and behavioral factors can cause an imbalance of vaginal microbiota (De Seta et al, 2014). This imbalance may also be induced by alterations in sex hormones during HE (Bradley et al, 2018;An et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones strongly affect the overall structure and function of vaginal microbiota (Hillier, 2011;Kaur et al, 2020). In general, vaginal microbiota is relatively balanced and stable, whereas genetic, ethnic, environmental, and behavioral factors can cause an imbalance of vaginal microbiota (De Seta et al, 2014). This imbalance may also be induced by alterations in sex hormones during HE (Bradley et al, 2018;An et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study among 60 Italian women, 30 who agreed to COC use and 30 who agreed to CVR use, found no difference in incident BV or intermediate vaginal flora over 6 months between the two groups. 33 , 34 In both of the aforementioned studies, women were analyzed according to chosen/assigned contraceptive method, allowing for discontinuations. Two studies among 151 Kenyan and 1,027 Ugandan female sex workers followed for ~1 to ~2 years respectively, found no significant difference in BV among women using COCs as compared to women using no contraception/(had tubal ligation, Kenya study only) while controlling for time-varying contraceptive use.…”
Section: Resultsmentioning
confidence: 99%
“…In a study among 60 COC users, women using a 17β-estradiol/nomegestrol regimen had a significant decrease in BV over time, though no information is provided on whether or not BV treatment was administered for women who were determined to have BV at baseline, or during the follow-up period. 34 A sub-study within a BV-treatment trial of 400 women found that current/recent users of estrogen-containing contraceptive (ECC) (n=110, among which 108 were oral contraceptive users and two were NuvaRing users) had significantly lower risk (aHR 0.51 [95% CI 0.33–0.78]) of BV recurrence over 6 months compared to women not reporting current/recent ECC use. 37 Lastly, a study among 6,109 women aged 18–35 in Zimbabwe, Uganda and Thailand, which included 15–24 months of follow-up per woman and time-varying control of contraceptive method, also observed a protective association (aHR 0.90, [95% CI 0.84, 0.97]) as compared to women not using hormonal contraception.…”
Section: Resultsmentioning
confidence: 99%
“…The findings suggest that the status of the vaginal microbiota and the formation or deposition of biomass on VR are inter-related. The authors noted that VRs releasing pregnancy prevention hormones may be important for protection of the vaginal microbiota during ring use; this hypothesis has been promoted by other researchers [213][214][215].…”
Section: Nuvaring ®mentioning
confidence: 97%